RNA m6A Modification Plays a Key Role in Maintaining Stem Cell Function in Normal and Malignant Hematopoiesis - Wang, Peipei; Feng, Mengdie; Han, Guoqiang; Yin, Rong; Li, Yashu; Yao, Shuxin; Lu, Pengbo; Wang, Yuhua; Zhang, Haojian (Frontiers in Cell and Developmental Biology, 2021)
N6-methyladenosine (m6A) is a commonly modification of mammalian mRNAs and plays key roles in various cellular processes. Emerging evidence reveals the importance of RNA m6A modification in maintaining stem cell function in normal hematopoiesis and leukemogenesis. In this review, we first briefly summarize the latest advances in RNA m6A biology, and further highlight the roles of m6A writers, readers and erasers in normal hematopoiesis and acute myeloid leukemia. Moreover, we also discuss the mechanisms of these m6A modifiers in preserving the function of hematopoietic stem cells (HSCs) and leukemia stem cells (LSCs), as well as potential strategies for targeting m6A modification related pathways. Overall, we provide a comprehensive summary and our insights into the field of RNA m6A in normal hematopoiesis and leukemia pathogenesis.